Tiếng Anh cho người đi du lịch nước ngoài (2011)
Unit 1: At the Travel Agent Unit 2: At the Airport Unit 3: Asking for Assistance Unit 4: At the Hotel Unit 5: At the Restaurant Unit 6: At the Bar Unit 7: Using Different kind of Services Unit 8: Concierge Unit 9: Sight Seeing Unit 10: Stopping a Passersby